2016
DOI: 10.17135/jdhs.2016.16.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Food Intake Ability and the Number of Remaining Teeth on Oral Health Related Quality of Life in Some Elderly People

Abstract: Eating supports to gain energy and nutrition and improves quality of life. Ageing affects the food intake ability due to loss of natural teeth and the progressive muscle degeneration. Our objective was to investigate how the food intake ability (FIA) and the remaining teeth could influence on oral health related quality of life in the elderly. This study was performed with 503 elderly subjects living in Daejeon, Korea. The questionnaire with the FIA with 30 Korean food and Oral Health Impact Profile 14 (OHIP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…All participants in our study had an average of >26 of 32 permanent teeth. This number is relatively high for older adults aged 65–85 years, considering that a recent cross-sectional survey [ 35 ] reported that the average number of teeth required to eat all kinds of food was at least 20. Additionally, a US survey conducted among individuals aged 65–69 years found that the participants had only 18 teeth remaining on average [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…All participants in our study had an average of >26 of 32 permanent teeth. This number is relatively high for older adults aged 65–85 years, considering that a recent cross-sectional survey [ 35 ] reported that the average number of teeth required to eat all kinds of food was at least 20. Additionally, a US survey conducted among individuals aged 65–69 years found that the participants had only 18 teeth remaining on average [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, the senior population is growing quickly as a result of declining birth rates and rising life expectancy; in 2020, it was 15.8%, and by 2060, it is expected to rise to 43.9% [ 1 ]. Physical changes due to aging include loss of natural teeth, weakening of coordination of body movements, and weakening of mastication muscles [ 2 ]. As a result, symptoms, such as poor appetite, decreased chewing, and swallowing function lead to nutritional imbalance.…”
Section: Introductionmentioning
confidence: 99%